Analysis of Website Quality Using The Webqual 4.0 Method at SMA Negeri 12 Tangerang - Wirna, Risalah Sabila; Hidayat, Rachmat; Verawati, Ellya (SAN Scientific, 2023)
Currently, information technology has become a determining factor for success in all aspects. This web media is a suggestion that can be used in schools where websites are used to convey information to students and the general public. SMA Negeri 12 Tangerang Regency is one of the educational institutions that wants to ensure that their website provides a satisfying experience to its visitors. By conducting a webqual 4.0 analysis, SMA Negeri 12 Tangerang Regency can gain deeper insight into the strengths and weaknesses of the website. This research aims to measure the quality of the website of SMA Negeri 12 Tangerang Regency based on the webqual 4.0 dimension variables, namely quality of use, quality of information, and quality of interaction. The method used in this research uses a quantitative method with stages of identifying webqual 4.0 variables, sample selection, data collection, data analysis, data interpretation, and validation. With the results of this research, you can carry out reliability testing, hypothesis testing, t test and f test. So the results can be concluded that during the t test the variables X1, variable Y.